CORRELATION OF SERUM VISFATIN LEVELS WITH DYSLIPIDEMIA IN OBESE BALB/C MICE - Naz, Raisa; Tauqeer, Shazia; Haleem, Nadia; Ayub, Muhammad (Pakistan Journal of Physiology, 2018)
Background: Visceral adipose tissues secrete several adipocytokines that modulate on their own way the extreme obesity, diabetes, dyslipidemia, atherosclerosis and inflammation. Visfatin is newly identified adipocytokine that is released by visceral adipose tissue. Its levels markedly increase during development of obesity. The aim of this study was to determine the levels of visfatin and its association with dyslipidemia in obese albino mice. Methods: It was a quasi experimental study. Sixty (60) Balb/c strain albino mice were divided into two groups of 30 each. Group I was taken as control non obese mice while Group II animals were fed high fat/high carbohydrate diet. Blood samples were collected to measure Total Cholesterol (TC), Triglycerides (TG), High Density Lipoprotein (HDL-C), Low Density Lipoprotein (LDL-C), Very Low Density Lipoprotein (VLDL-C) and visfatin levels. Results: There was significant correlation among different classes of lipids with increasing visfatin levels in diet induced obese mice (p<0.05). TC, TG, LDL and VLDL showed significant elevation in serum levels (5.94±1.18 mmol/L, 2.92±0.15 mmol/L, 3.91±0.56 mmol/L, 1.56±0.31 mmol/L respectively) against controls (3.1±0.40 mmol/L, 1.62±0.01 mmol/L, 1.82±0.432 mmol/L, 0.60±0.13 mmol/L correspondingly). Pearson’s correlation coefficient between rising serum visfatin and various classes of lipids showed strong positive correlation between visfatin and TC, TG, LDL, and VLDL, while negative correlation with serum HDL levels (p<0.05). Conclusion: Increased serum visfatin levels are strongly associated with obesity and dyslipidemia. Keywords: Visfatin, obesity, adipocytokines, dyslipidemia Pak J Physiol 2018;14(1):27–9